2021
DOI: 10.1094/pdis-01-21-0037-re
|View full text |Cite
|
Sign up to set email alerts
|

Penicillium and Talaromyces Species as Postharvest Pathogens of Pear Fruit (Pyrus communis) in Serbia

Abstract: Pears are one of the oldest and the third most important fruit species grown in temperate regions. They are consumed because of their nutritional and health benefits, in fresh form or as various processed products. This paper resolves the etiology of the Penicillium-like mold symptoms on pear fruits in Serbia. Samples of pear fruits with blue mold and other Penicillium-like mold symptoms were collected in Serbia from 2016 to 2019, from four storages. The recovered isolates were identified and characterized usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…causing postharvest rot resulted in confirmatory and novel findings. Penicillium expansum and P. crustosum caused blue mold on stored apple and pears which is congruent with previous studies [20][21][22][23][24]55], while blue mold on quince caused by P. expansum, P. crustosum and P. solitum is a novel find in Serbia. Additionally, P. crustosum has not been identified on medlar nor quince, indicating two new hosts for this blue mold causing species.…”
Section: Discussionsupporting
confidence: 91%
“…causing postharvest rot resulted in confirmatory and novel findings. Penicillium expansum and P. crustosum caused blue mold on stored apple and pears which is congruent with previous studies [20][21][22][23][24]55], while blue mold on quince caused by P. expansum, P. crustosum and P. solitum is a novel find in Serbia. Additionally, P. crustosum has not been identified on medlar nor quince, indicating two new hosts for this blue mold causing species.…”
Section: Discussionsupporting
confidence: 91%
“…Barkai-Golan (1974) conducted a research in Israel and confirmed this species as capable to cause lesions on fruits of apple, pear, grape and tomato. In one of our previous studies (Stošić et al, 2021) we identified T. rugulosus as spoilage agents of stored pear fruits in Serbia. Pitt and Hocking (2009) claim that this species could be pathogenic on plants probably more then the current data suggest.…”
Section: Resultsmentioning
confidence: 94%
“…[23,81], which are the dominant producers of funicones, the possible release of these compounds in plant products may arise during the postharvest phase, where the biosynthetic aptitudes can be boosted along with the saprophytic development. Recent reports of these fungi as postharvest pathogens concern T. albobiverticillius on pomegranate [82], T. rugulosus on grapes [83], T. minioluteus on onion bulbs and quince, orange, and tomato fruit [84], and both of the latter two species on pears [85]. Although none of these species are known to produce funicones, it is quite possible that other Talaromyces spp.…”
Section: Potential Role Of Funicone-like Compounds As Mycotoxinsmentioning
confidence: 99%